2015
DOI: 10.1016/j.oceaneng.2015.09.052
|View full text |Cite
|
Sign up to set email alerts
|

A large scale model experimental study of a tidal turbine in uniform steady flow

Abstract: An experimental study measuring the performance and wake characteristics of a 1:10 th scale horizontal axis turbine in steady uniform flow conditions is presented in this paper.Large scale towing tests conducted in a lake were devised to model the performance of the tidal turbine and measure the wake produced. As a simplification of the marine environment, towing the turbine in a lake provides approximately steady, uniform inflow conditions. A 16m long x 6m wide catamaran was constructed for the test programme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Due to the orientation of the ADV and the fact that the in-axis flow component is correlated from two signals, the vertical velocity component is inherently less noisy than the horizontal components. This explains why the horizontal spectra flatten due to noise at lower frequency than the vertical spectrum [25], [26]. Although not directly comparable in magnitude, the ADV data shown in Fig.…”
Section: Overlapping Adv and Microrider Spectral Outputmentioning
confidence: 83%
“…Due to the orientation of the ADV and the fact that the in-axis flow component is correlated from two signals, the vertical velocity component is inherently less noisy than the horizontal components. This explains why the horizontal spectra flatten due to noise at lower frequency than the vertical spectrum [25], [26]. Although not directly comparable in magnitude, the ADV data shown in Fig.…”
Section: Overlapping Adv and Microrider Spectral Outputmentioning
confidence: 83%
“…Further, the identified location by TSE index is tested by Ramos and Iglesias on two different types of turbines, ie, Gorlov helicoidal turbine and Evopod. Evopod is an axial‐flow horizontal‐axis turbine that operates under buoyant mooring arrangement as shown in Figure . Turbine efficiency, availability, capacity factor, and total energy output are the four parameters considered for comparison.…”
Section: Review On Hydrokinetic Potential Assessmentmentioning
confidence: 99%
“…Evopod is an axial-flow horizontal-axis turbine that operates under buoyant mooring arrangement as shown in Figure 6. 54 Turbine efficiency, availability, capacity factor, and total energy output are the four parameters considered for comparison. It was observed that although being an axial-flow turbine, Evopod has higher efficiency and thus generates higher output but has less availability and capacity factor than does Gorlov helicoidal turbine.…”
Section: Types Of Hydrokinetic Devicesmentioning
confidence: 99%
“…Deployment of tidal energy devices are planned to harness energy in the tidal channel of Ria Formosa, Portugal, although the same challenge is faced as the site is limited to a current velocity of 1.4 m/s. Initial deployment tests were performed showing underutilisation of the small-scale Evopod turbine [14,15], with a maximum output below 25% of the rated power output [16].…”
Section: Introductionmentioning
confidence: 99%